AUTOMATIC HELMET WIPER - RAJU, K.; KRISHNA, B.BALA; ASMA, MD.; BHARGAVI, D.; RATNAKAR, J. (The journal of contemporary issues in business and government, 2022)
An improvised helmet design which is integrated with a circuitry for automatic rain sensing mini wiper located on the eye shield. The presence of a automatic helmet wiper will make two wheeler riding easier and safer in rainy season, since the driver won’t be bothered by the continuous rain drops disturbing his/her vision. The wiper will automatically start as soon as it detects the presence of rain drops on the rain sensor mounted on the top of the helmet. This makes the rider to drive safety in the rain.